Dynamic Asset Allocation under Inflation - Brennan, Michael J.; Xia, Yihong (Journal of Finance, 2002)
ABSTRACT We develop a simple framework for analyzing a finite‐horizon investor's asset allocation problem under inflation when only nominal assets are available. The investor's optimal investment strategy and indirect utility are given in simple closed form. Hedge demands depend on the investor's horizon and risk aversion and on the maturities of the bonds included in the portfolio. When short positions are precluded, the optimal strategy consists of investments in cash, equity, and a single nominal bond with optimally chosen maturity. Both the optimal stock‐bond mix and the optimal bond maturity depend on the investor's horizon and risk aversion.